Keterampilan Berpikir Kritis dalam Pembelajaran Berbasis Masalah Berbantuan Situs Jejaring Sosial Edmodo - Siti Rosiyanah (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The rapid development of informatics and computer (ICT) techniques has an impact on education today. On the other hand, the changing paradigm of education that used to embrace teacher-centered learning into student-centered learning has brought significant changes to the learning methods developed today. This study aims to determine the effectiveness of problem-based learning models assisted by Edmodo social networking site on critical thinking skill and student learning outcomes. This research was conducted in class VIII of SMP Negeri 6 Jepara in the odd semester of 2019/2020 Academic Year on the material of pressure and its application in daily life. The research design used was the pre-test and post-test control group design. Data retrieval is done by observation, documentation and tests. The results showed that the value of tcount critical thinking skills and student learning outcomes > ttable value (1.99). The value of tcount critical thinking skills and learning outcomes respectively is 11.12 and 2.757. The result of this study concluded that the problem based learning model supported by Edmodo’s social networking site is effective to improve critical thinking skills and students learning outcomes.